Effect of The PBL Model Accompanied by Multi-Representation-Based Science Worksheets on Learning Outcomes - Annisa Mauliya; I Ketut Mahardika; Zainur Rasyid Ridlo (Universitas Negeri Padang, 2023)
This study aims to examine the significant effect on learning outcomes and the effectiveness of learning by using the PBL learning model accompanied by multi-representation-based science worksheets in grade 8 junior high school students. This research is based on low learning outcomes, students who are less active in learning and students' difficulties in answering questions in image, verbal and graphic formats. The research method used was a quasi-experimental design with a post-test only control group. Data was collected through written tests and response questionnaires. The normality test results for the post-test scores for the experimental and control classes were 0.197 and 0.200, which means these values are normal. The results of applying the PBL learning module accompanied by multi-representation-based Science Worksheets obtained data in the form of post-test scores which were tested using an independent sample t-test. The results of the independent sample t-test obtained a value of 0.00. The results of the questionnaire analysis showed that students responded very positively with an average value of 95%. The results of this test indicate that students more easily understand learning material, are active and interested in learning. Based on the results obtained, it can be concluded that the PBL learning model accompanied by multi-representation-based IPA worksheets has a significant effect on student learning outcomes and is very effectively used in the science learning process in junior high schools. PBL models with a multiple representations can assist students overcoming challenges in problem-solving via the PBL model's processes, also when using different representations.